Aging does not affect auditory motion discrimination based on interaural level differences - Shinya Harada; Ryo Teraoka; Naoki Kuroda; Wataru Teramoto (i-Perception)
It is well known that aging affects fundamental perceptual functions. Numerous studies have investigated age-related changes in visual motion perception and demonstrated that aging impairs motion processing. However, limited studies have explored age-related changes in auditory motion perception, and whether aging influences auditory motion perception based on interaural level differences remains unknown. This study examined age-related differences in the discrimination of auditory motion direction based on interaural level differences. We conducted two experiments to estimate the signal-to-noise ratio and motion coherence thresholds required to discriminate auditory motion and visual motion directions, respectively, in younger and older adults. Results showed that age significantly impairs visual motion discrimination; however, it does not impair auditory motion discrimination. These findings suggest that aging does not affect auditory motion perception based on interaural level differences, at least with the broadband noise used in this experiment.